Studi potensi wisata pantai Pemuda Jimbaran, Kecamatan Kuta Selatan, Kabupaten Badung - Nainggolan, Yosephyn; Utami, Ni Wayan Febriana; Gunadi, I Gusti Alit (Jurnal Arsitektur Lansekap, 2020)
Study on potency of Pemuda beach in Jimbaran, Southern Kuta District, Badung Regency. Pemuda beach is one of tourism destination located in Jimbaran which has a beautiful natural condition and also unique. Otherwise, only few people visit this place due to lack of information that tourists have such as hidden location of the beach and confusing boundaries of the beach from tourism properties. Therefore this research has a purpose to explore a potency that Pemuda beach has and also to investigate it potency and develop it using the 4A+1C concept. The method used was survey with several data collection techniques such as observation, interview, questionnaires and literature study. Then, data analyzed descriptively to explain the site potential which refers to the complete potential study process. Results indicated that the biophysical aspects (i.e. climate, soil, topography, visual description and also vegetation and animals) and socio-cultural aspects of the region have opportunity to be developed as tourist areas. This studi also illustrated that attractions, accessability, amenities, ancilliary and community involvement for Pemuda beach were potencially to be developed. Hence, by understanding the potentials and the possibility to develop the area, this study expected to give more knowledge to the visitor. Further, it is also recommended to local society together with the government to use this exploration study as an additional reference to develop the beach.